2021
DOI: 10.1152/japplphysiol.00056.2021
|View full text |Cite
|
Sign up to set email alerts
|

CORP: quantification of human skeletal muscle carnosine concentration by proton magnetic resonance spectroscopy

Abstract: Non-invasive techniques to quantify metabolites in skeletal muscle provide unique insight into human physiology and enable the translation of research into practice. Proton magnetic resonance spectroscopy (1H-MRS) permits the assessment of several abundant muscle metabolites in vivo, including carnosine, a dipeptide composed of the amino acids histidine and beta-alanine. Muscle carnosine loading - accomplished by chronic oral beta-alanine supplementation - improves muscle function, exercise capacity and has pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Given the fact that high proportions of type-I fibers are suggested to display greater mechanical efficiency at common movement frequencies (i.e., 1-2Hz, e.g., cycling between 60 and 120 rpm) that are close to the type-I fiber's peak efficiency velocity (He et al, 2000;Joyner and Coyle, 2008), a higher percentage of type-I fibers would relate to a higher gross efficiency (Coyle et al, 1992;Horowitz et al, 1994), and therefore contributes to a higher endurance performance (Horowitz et al, 1994). Nowadays, non-invasive techniques such as 1 H-MRS measurements of muscle carnosine content are also used to estimate type-I and II muscle typology, thereby confirming prior muscle biopsy-based findings across athletes (Baguet et al, 2011;Bex et al, 2017;Lievens et al, 2020Lievens et al, , 2021.…”
Section: Muscle Fiber Typesupporting
confidence: 52%
“…Given the fact that high proportions of type-I fibers are suggested to display greater mechanical efficiency at common movement frequencies (i.e., 1-2Hz, e.g., cycling between 60 and 120 rpm) that are close to the type-I fiber's peak efficiency velocity (He et al, 2000;Joyner and Coyle, 2008), a higher percentage of type-I fibers would relate to a higher gross efficiency (Coyle et al, 1992;Horowitz et al, 1994), and therefore contributes to a higher endurance performance (Horowitz et al, 1994). Nowadays, non-invasive techniques such as 1 H-MRS measurements of muscle carnosine content are also used to estimate type-I and II muscle typology, thereby confirming prior muscle biopsy-based findings across athletes (Baguet et al, 2011;Bex et al, 2017;Lievens et al, 2020Lievens et al, , 2021.…”
Section: Muscle Fiber Typesupporting
confidence: 52%
“…Other practices, such as reporting individual data and spectrum, SNR, and carnosine peak width will help to promote transparency. We maintain, like Lievens et al (1), that the 1 H-MRS determination of muscle carnosine concentrations is important in the field of human physiology, but only if it is shown to be valid and reliable.…”
mentioning
confidence: 63%
“…We quantified muscle carnosine with 1 H-MRS (5) using the same procedures as previously described (7) and showed poor agreement between 1 H-MRS and a reference method. Lievens et al (1) suggested that this could be explained by the small voxel size used in our study, leading to a lower signal-to-noise ratio (SNR). Noteworthy, all our 41 measurements displayed an SNR above their proposed (7) cut-off of SNR > 3 (SNR: 7.1 ± 2.4, min = 3.5, max = 14.2), meaning that voxel size does not account for the poor validity of 1 H-MRS shown in our study.…”
mentioning
confidence: 78%
See 2 more Smart Citations